INTEGRALISME ILMU DALAM ISLAM (SEJARAH PERKEMBANGAN DAN KLASIFIKASI) - Iis Uun Fardiana (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2017)
One method in the process of Islamic knowledge is integralization. While integralism sees that integralization is the integration of the richness of human knowledge with revelation (Allah’s guidance in the Qur’an and its implementation in the Sunnah of the Prophet). Integralistic science is the science that unites (not merely combines) God’s revelation and the discovery of the human mind. The integralistic sciences will not exclude God (secularism) or exclude humans (other worldly asceticism). It is hoped that integralism will simultaneously resolve the conflict between extreme secularism and radical religions in many sectors. The idea of Islamization of science emerged as a response to the dichotomy between the science of religion and science which entered the secular West and the culture of modern society into the Islamic world. The progress that modern science has made has a remarkable effect, but on the other hand it also has a negative impact, because modern science (West) is dry value apart from religious values. In addition, Islamization of Science is also a reaction to the crisis of educational system faced by Muslims, namely the dualism of Islamic education system and modern education (secular) that confuses Muslims. Keyword: Integration, Science, Islam